Is ICI-based therapy better than chemotherapy for metastatic NSCLC patients who develop EGFR-TKI resistance? A real-world investigation - Cheng, Yajie; Yang, Bin; Ouyang, Wen; Jie, Chen; Zhang, Wei; Chen, Gang; Zhang, Junhong; Yu, Jing; Xie, Conghua (Frontiers in Oncology, 2022)
Purpose: To evaluate the outcomes of immune checkpoint inhibitors (ICIs) based treatments versus classical chemotherapy for metastatic non-small cell lung cancer (NSCLC) patients who develop epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI) resistance and to explore the population that may benefit from ICI-based therapy. Materials and methods: All patients who had previously received EGFR-TKI therapy at two cancer centers in China and developed resistance to targeted therapies were included. Progression-free survival (PFS) and overall survival (OS) were utilized to evaluate the outcomes of the study cohort. Results: A total of 132 patients were included. The median follow-up time for this cohort was 21.7 months (IQR, 14.8-28.8 months), calculated from the date of EGFR-TKI resistance. The median PFS and OS were 4.9 months (IQR, 2.8–9.2) and 13.5 months (IQR, 6.6–26.5 months), respectively. Multivariate analysis showed that ICI-based therapy could significantly improve OS when compared to the classic chemotherapy (hazard ratio [HR], 0.55; 95% CI, 0.34-0.88; P = 0.01) after adjusting for variables such as gender, age, mutation status, and brain or liver metastases status. The combined modality of ICI plus chemotherapy could offer a long-term OS benefit in most subgroups, such as young (<65 years) patients, and those without secondary T790M mutations or absence of liver and brain metastases, and the populations with good Eastern Cooperative Oncology Group (ECOG) scores. Conclusion: For patients presenting with EGFR-TKI resistance, ICI-based therapy could offer a more favorable survival than classical chemotherapy. The combination of ICI with chemotherapy may be the optimal modality for those with good ECOG PS scores.